Entrepreneurship Education Management in Improving Student's Independence at Vocational Collection - Suharjono; Waska Warta; Iim Wasliman; Sutaryat Trisnamansyah (Journal of Islamicate Studies, 2022)
Management of entrepreneurship education in higher education, especially at vocational universities in this study was built to build effective policy development in the higher education environment in showing its form of productivity in producing quality human resources by cultivating entrepreneurial values ??which are the basic values ??for building job opportunities for students. This realization itself is built through an understanding of values, where the potential of human resources is potentially built and developed in a projected manner. In addition to developing values, where the world of education is built in a fundamental transformation in order to build student entrepreneurship skills that are directed and integrated with the education they carry out, as the basis for applying discipline values ??and developing the value of their competencies.